Alexander Kiosev’s Concept of Self-colonization and the Symmorphic Effect - Szwat-Gyłybowa, Grażyna (Poznańskie Studia Slawistyczne, 2017)
Stemming from the general postcolonial theoretical tradition, the concept of self-colonisation proposed by the Bulgarian scholar Alexander Kiosev has proved inspiring to Polish scholars. This article attempts to examine more closely Kiosev’s meandering self-reflective musings on what he called his “metaphor” of self-colonization, an idea he ultimately rejected in view of the undesirable ressentiment it tends to produce. By illustrating the historical and cultural background underpinning the concept of self-colonisation I seek to identify the roots of potential intercultural misunderstanding. Above all, I focus on the consequences of the teleological approach inherent in Kiosev’s concept. Those are expressed in identifying manufactured (sic!) origins with an account which can be couched in the language of a politically and therapeutically conditioned method of research. This leads to a symmorphic deformation of those origins, aligned to the requirements of the modern world.